Ex post analysis of road projects: resilience to crisis - Ćirilović, Jelena; Nikolić, Ana; Mikić, Miljan; Mladenović, Goran (European Journal of Transport and Infrastructure Research, 2018)
This investigation aimed to reveal a mechanism of how different road projects' settings respond to macro-economic crisis. Qualitative and quantitative analyses were performed over a sample of 31 European road projects, in various funding arrangements and life cycle phases, all extracted from the Horizon 2020 BENEFIT project cases database. The project setting is described through a specific combination of project features and/or values of developed indicators. The analysis was applied to identify factors that contributed to projects’ performance regarding the resilience to the global financial crisis of 2007–2008. By doing this, it became possible to determine potential liabilities of projects that are already in their implementation or use phases. The analysis showed there are equally strong contributors to a project’s success within country-specific, as well as project-specific features. In order to boost resilience toward sudden and unpredicted disruptions, several factors have emerged, such as long term planning, investing in top priority projects (preferably medium size investments), with realistic traffic projections and experienced and responsible concessionaires, but also having in place strong regulatory bodies and government support.The identified mechanism of enhancing the resilience to crisis caused by a specific project setting can be beneficial to multiple stakeholders.